From APCELL to ACELL and beyond - Expanding a multi-institution project for laboratory-based teaching and learning - Jamie, I.; Read, J.; Barrie, S.; Bucat, R.; Buntine, Mark; Crisp, G.; George, A.; Kable, S. (The Royal Australian Chemical Institute, 2007)
The advancing chemistry by enhancing learning in the laboratory (APCELL) project is a well-established, multi-institution, collaborative project contributing to improvements in the quality of laboratory-based teaching and learning. ACELL is an expansion of the previous APCELL project and now encompasses all areas of undergraduate chemistry. It contributes to quality improvement in laboratory learning directly by providing a database of educationally sound, peer-reviewed, and student-tested undergraduate laboratory experiments. Testing of experiments is generally carried out at dedicated workshops, such as the one held in Sydney in February 2006, at which 33 experiments from 27 different Universities from Australia and New Zealand were evaluated. In addition, by contributing to the professional development of chemistry academic staff by expanding their understanding of issues surrounding student learning, by fostering the development of a community of pedagogically aware educators, and by providing tools for analysing and documenting teaching experiments, the ACELL project has the potential to catalyse the improvement of experiments not directly reviewed by the project. This paper reviews the evolution of ACELL, its current position, and provides some suggestions for future developments.